Effect of Double-Ovsynch and Presynch-Ovsynch on postpartum ovarian cysts and inactive ovary in high-yielding dairy cows - Li, Ziyuan; Luan, Shuyi; Yan, LongGang; Xie, Chengyun; Lian, Zhengjie; Yang, Mingmao; Mei, Minmin; Lin, Pengfei; Wang, Aihua; Jin, Yaping (Frontiers in Veterinary Science, 2024)
Optimizing the management of dairy cattle reproduction can reduce postpartum ovarian disease in high-yielding dairy cows and thus enhance ranch economic benefit. The hypothesis of this study was that the Double-Ovsynch (DO) protocol in high-producing dairy cows would result in a lower incidence of follicular cysts but a higher incidence of luteal cysts compared to those undergoing the Presynch-Ovsynch (PS) protocol. In this experiment, 384 cows (204 primiparous and 180 multiparous) were allocated to the DO group, which followed the protocol:GnRH-7d-PGF2α-3d-GnRH-7d-Ovsynch-56h(GnRH-7d-PGF2α-56h-GnRH-16hTAI), starting on 39±3 days in milk (DIM). Additionally, 359 cows (176 primiparous and 183 multiparous)